Effects of Iron-Steel Factory and Dense Traffic on Leaf Chemical Compounds of Six Tree Species in Turkey - Turfan, Nezahat; Savaci, Gamze; Sarıyıldız, Temel (Kastamonu University, 2018)
Abstract

Aim of study: Tree
planting can play an important role in improving the quality of the urban
environment. On the other hand, air pollutants can affect growth and health of
trees. We studied the impacts of air pollution caused by the iron- steel
factory and dense traffic on leaf chemical composition and also tree tolerance
to the air pollution using six tree species (Maple, Ash tree, Cypress, Black
pine, Sycamore and Aspen).

Material and Methods: The fresh leaf and
needle sampling was carried out in April and July, and analyzed for
photosynthetic pigments, peroxidation level, hydrogen peroxide, enzymatic
antioxidants and non-enzymatic antioxidants.

Main results: Although there were
statistically significant variations in the studied chemical compositions of
the fresh leaf and needle samples between the six tree species, the pollution
types and time, each chemical factor acted different ways with the pollution
types and time according to tree species. In general, the pigment values, MDA,
H2O2 and APX, concentrations in July were lower than
those in April, whereas CAT, SOD, proline and protein concentrations in July
were higher than those in April. Maple tree was more resistant to the traffic
pollution, while Ash tree was more tolerant to both the pollution types. Among
all trees, Aspen was found more susceptible to the traffic pollution

Research highlights: The results could be
used in the future research directions to improve our understanding of the role
of individual tree species in air pollution reduction and also set up a
healthy, well managed urban forest which can provide many ecological benefits
to urban environment.
Keywords: Iron-steel factory; Air pollution; Chemical composition; Forest tree; Dense traffic; 13. Climate action; 11. Sustainability; 15. Life on land